Optical laminate and display system
The optical laminate in VR goggles optimizes weight reduction and visibility by using a polarizing member with specific expansion coefficients and elastic modulus properties, enhancing image display performance.
Patent Information
- Application Number
- JP2023152016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
There is a demand for lightweight VR goggles with improved visibility, and existing optical laminates do not effectively balance weight reduction with enhanced image display performance.
An optical laminate comprising a polarizing member, a first λ/4 member, a half mirror, and a reflective polarizing member, with specific expansion coefficients and elastic modulus properties, is designed to enhance visibility while reducing weight by optimizing the optical path and minimizing dimensional changes due to temperature variations.
The optical laminate achieves a significant reduction in weight while improving visibility and maintaining optical performance under varying temperatures, addressing the challenges faced by conventional VR goggles.
Smart Images

Figure 2025044449000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical stack and a display system. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as retardation members and polarizing members are generally used to realize image display and improve image display performance (see, for example, Patent Document 1). These optical members can be integrated in advance and mounted on the image display device as an optical laminate.
[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays (VR goggles) for realizing Virtual Reality (VR) have begun to be commercialized. Since VR goggles are being considered for use in various situations, there is a demand for them to be lightweight and have improved visibility. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]
[0005] The weight reduction of the VR goggles can be achieved, for example, by thinning the lenses used in the VR goggles. On the other hand, there is also a demand for the development of an optical laminate including the optical member suitable for a display system using lenses.
[0006] In view of the above, a main object of the present invention is to provide an optical laminate that can effectively achieve weight reduction of VR goggles while improving visibility. [Means for solving the problem]
[0007] 1. An optical laminate according to an embodiment of the present invention is an optical laminate used in a display method comprising the steps of: passing light representing an image outputted via a polarizing member through a first λ / 4 member; passing the light that has passed through the first λ / 4 member through a half mirror and a first lens unit; passing the light that has passed through the half mirror and the first lens unit through a second λ / 4 member; reflecting the light that has passed through the second λ / 4 member toward the half mirror with a reflective polarizing member; and allowing the light reflected by the reflective polarizing member and the half mirror to pass through the reflective polarizing member by the second λ / 4 member. The optical laminate comprises the polarizing member, a first phase difference member including the first λ / 4 member, and a pressure-sensitive adhesive layer disposed between the polarizing member and the first phase difference member, and the linear expansion coefficient of the polarizing member at 25° C. to 65° C. in the absorption axis direction is −1.9×10 -4 / °C or less, the first λ / 4 member is a liquid crystal alignment solidified layer, and the pressure-sensitive adhesive layer has an elastic modulus at 85°C of 0.07 MPa to 0.5 MPa. 2. In the optical laminate described in 1 above, the linear expansion coefficient of the first phase difference member in the absorption axis direction of the polarizing member is 0.6×10 -4 / °C or more. 3. In the optical laminate according to 1 or 2 above, the first λ / 4 member may have a thickness of 5 μm or less. 4. In the optical laminate according to any one of 1 to 3 above, the first retardation member may further include another retardation layer. 5. In the optical laminate described in any one of 1 to 4 above, the absolute value of the difference between the linear expansion coefficient of the polarizing member in the absorption axis direction at 25 ° C. to 65 ° C. and the linear expansion coefficient of the polarizing member in the absorption axis direction of the first phase difference member in the optical laminate at 25 ° C. to 65 ° C. is 2.5 × 10 -4 / °C or more. 6. In the optical laminate according to any one of 1 to 5 above, the absolute value of the difference between the linear expansion coefficient of the polarizing member in the transmission axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member in the transmission axis direction of the first phase difference member in the optical laminate at 25° C. to 65° C. is 1.1×10 -4 / °C or more. 7. In the optical laminate described in any one of 1 to 6 above, the ratio of the absolute value of the difference between the linear expansion coefficient at 25°C to 65°C in the absorption axis direction of the polarizing member and the linear expansion coefficient at 25°C to 65°C in the absorption axis direction of the polarizing member of the first phase difference member when made into the optical laminate to the absolute value of the difference between the linear expansion coefficient at 25°C to 65°C in the transmission axis direction of the polarizing member and the linear expansion coefficient at 25°C to 65°C in the transmission axis direction of the polarizing member of the first phase difference member when made into the optical laminate may be 0.6 or less.
[0008] 8. A display system according to an embodiment of the present invention is a display system that displays an image to a user, comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member that is arranged in front of the display element and reflects the light emitted from the display element; a first lens unit that is arranged on an optical path between the display element and the reflective polarizing member; a half mirror that is arranged between the display element and the first lens unit and transmits the light emitted from the display element and reflects the light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member that is arranged on the optical path between the display element and the half mirror; and a second λ / 4 member that is arranged on the optical path between the half mirror and the reflective polarizing member; and an optical laminate having the polarizing member, a first phase difference member including the first λ / 4 member, and a pressure-sensitive adhesive layer that is arranged between the polarizing member and the first phase difference member, The linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. is −1.9×10 -4 / °C or less, the first λ / 4 member is a liquid crystal alignment solidified layer, and the pressure-sensitive adhesive layer has an elastic modulus at 85°C of 0.07 MPa to 0.5 MPa. 9. In the display system described in the above item 8, the linear expansion coefficient of the first phase difference member in the absorption axis direction of the polarizing member when the optical laminate is formed is 0.6×10 -4 / °C or more. 10. In the display system described in the above item 8 or 9, the first λ / 4 member may have a thickness of 5 μm or less. 11. In the display system according to any one of the above items 8 to 10, the first retardation member may further include another retardation layer. 12. In the display system according to any one of the above items 8 to 11, the absolute value of the difference between the linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. of the first phase difference member when the optical laminate is formed is 2.5×10 -4 / °C or more. 13. In the display system according to any one of the above items 8 to 12, the absolute value of the difference between the linear expansion coefficient of the polarizing member in the transmission axis direction at 25° C. to 65° C. and the linear expansion coefficient of the first phase difference member in the transmission axis direction of the polarizing member when the optical laminate is formed is 1.1×10 -4 / °C. 14. In the display system described in any one of 8 to 13 above, the ratio of the absolute value of the difference between the linear expansion coefficient at 25°C to 65°C in the absorption axis direction of the polarizing element and the linear expansion coefficient at 25°C to 65°C in the absorption axis direction of the polarizing element of the first phase difference element when formed into the optical laminate to the absolute value of the difference between the linear expansion coefficient at 25°C to 65°C in the transmission axis direction of the polarizing element and the linear expansion coefficient at 25°C to 65°C in the transmission axis direction of the polarizing element of the first phase difference element when formed into the optical laminate may be 0.6 or less. 15. In the display system according to any one of the above items 8 to 14, the absolute value of the difference between the in-plane retardation (a) of the first λ / 4 component and the in-plane retardation (b) of the second λ / 4 component may be 3.5 nm or less. Effect of the Invention
[0009] According to the optical laminate according to the embodiment of the present invention, it is possible to effectively achieve a reduction in the weight of VR goggles while improving visibility. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing a general configuration of a display system according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a general configuration of an optical laminate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.
[0012] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise angles with respect to a reference direction unless otherwise specified. Thus, for example, "45°" means ±45°. In this specification, "substantially parallel" includes a range of 0°±10°, preferably within a range of 0°±5°, more preferably within a range of 0°±3°, and even more preferably within a range of 0°±1°. "Substantially perpendicular" includes a range of 90°±10°, preferably within a range of 90°±5°, more preferably within a range of 90°±3°, and even more preferably within a range of 90°±1°.
[0013] [Display System] FIG. 1 is a schematic diagram showing a schematic configuration of a display system according to one embodiment of the present invention. In FIG. 1, the arrangement and shape of each component of a display system 2 are typically illustrated. The display system 2 includes a display element 12, a reflector 14 including a reflective polarizing member, a first lens unit 16, a half mirror 18, a first λ / 4 member 20, a second λ / 4 member 22, and a second lens unit 24. The reflector 14 is disposed in front of the display surface 12a of the display element 12, and can reflect light emitted from the display element 12. The first lens unit 16 is disposed on the optical path between the display element 12 and the reflector 14, and the half mirror 18 is disposed between the display element 12 and the first lens unit 16. The first λ / 4 member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second λ / 4 member 22 is disposed on the optical path between the half mirror 18 and the reflector 14.
[0014] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member (typically, a polarizing film) that may be included in the display element 12, and is converted into a first linearly polarized light.
[0015] The first linearly polarized light incident on the first λ / 4 member 20 is converted into a first circularly polarized light. The first λ / 4 member 20 may be provided integrally with the display element 12. For example, the first λ / 4 member 20 may be provided integrally with a polarizing member that may be included in the display element 12.
[0016] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflecting portion 14 toward the reflecting portion 14. The half mirror 18 is provided integrally with the first lens portion 16.
[0017] The second λ / 4 member 22 can transmit the light reflected by the reflecting unit 14 and the half mirror 18 through the reflecting unit 14, which includes a reflective polarizing member. The second λ / 4 member 22 may be provided integrally with the first lens unit 16.
[0018] The first circularly polarized light output from the first λ / 4 member 20 passes through the half mirror 18 and the first lens unit 16, and is converted into the second linearly polarized light by the second λ / 4 member 22. The second linearly polarized light output from the second λ / 4 member 22 is reflected toward the half mirror 18 without passing through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the second linearly polarized light that is incident on the reflective polarizing member included in the reflecting unit 14 is the same as the reflection axis of the reflective polarizing member. Therefore, the second linearly polarized light that is incident on the reflecting unit 14 is reflected by the reflective polarizing member.
[0019] The second linearly polarized light reflected by the reflecting unit 14 is converted into the second circularly polarized light by the second λ / 4 member 22, and the second circularly polarized light emitted from the second λ / 4 member 22 passes through the first lens unit 16 and is reflected by the half mirror 18. The circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member 22. The third linearly polarized light passes through the reflective polarizing member included in the reflecting unit 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member included in the reflecting unit 14 is the same as the transmission axis of the reflective polarizing member. Therefore, the third linearly polarized light incident on the reflecting unit 14 passes through the reflective polarizing member.
[0020] The light transmitted through the reflecting portion 14 passes through the second lens portion 24 and enters the user's eye 26.
[0021] For example, the absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member included in the reflector 14 may be disposed approximately parallel to each other or approximately perpendicular to each other. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the first λ / 4 member 20 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the second λ / 4 member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.
[0022] The in-plane retardation Re(550) of the first λ / 4 member 20 is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm.
[0023] The first λ / 4 member 20 preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the first λ / 4 member 20 is, for example, less than 1, and may be 0.95 or less, or may be less than 0.90, or may be 0.85 or less. The Re(450) / Re(550) of the first λ / 4 member 20 is, for example, 0.75 or more.
[0024] In one embodiment, the first λ / 4 member 20 satisfies all of Re(400) / Re(550)<0.85, Re(650) / Re(550)>1.03, and Re(750) / Re(550)>1.05. The first λ / 4 member 20 preferably satisfies at least one selected from 0.65<Re(400) / Re(550)<0.80 (preferably, 0.7<Re(400) / Re(550)<0.75), 1.0<Re(650) / Re(550)<1.25 (preferably, 1.05<Re(650) / Re(550)<1.20), and 1.05<Re(750) / Re(550)<1.40 (preferably, 1.08<Re(750) / Re(550)<1.36), more preferably satisfies at least two, and still more preferably satisfies all of them.
[0025] The first λ / 4 member 20 preferably exhibits a refractive index characteristic showing a relationship of nx>ny≧nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the first λ / 4 member 20 is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0026] The thickness of the first λ / 4 member 20 is, for example, 20 μm or less, preferably 10 μm or less, more preferably 8 μm or less, still more preferably 6 μm or less, particularly preferably 5 μm or less, and may be 4 μm or less. By satisfying such a thickness, the first λ / 4 member 20 is excellent in smoothness and can contribute to improving the visibility of the display system. The thickness of the first λ / 4 member 20 is, for example, 1 μm or more.
[0027] The first λ / 4 member 20 is preferably composed of an oriented and fixed layer of a liquid crystal compound. By being composed of an oriented and fixed layer of a liquid crystal compound, the above thickness can be satisfactorily achieved. In addition, the uniformity of the in-plane retardation value can be excellent. Specifically, the uniformity of the in-plane retardation value can be excellent compared to a stretched film of a resin film.
[0028] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described later. In the first λ / 4 member, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first λ / 4 member (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.
[0029] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.
[0030] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.
[0031] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.
[0032] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.
[0033] The in-plane retardation Re(550) of the second λ / 4 member 22 is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm.
[0034] The second λ / 4 member 22 preferably exhibits an inverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the second λ / 4 member 22 is, for example, less than 1, and may be 0.95 or less, or may be less than 0.90, or may be 0.85 or less. The Re(450) / Re(550) of the second λ / 4 member 22 is, for example, 0.75 or more.
[0035] In one embodiment, the second λ / 4 member 22 satisfies all of Re(400) / Re(550) < 0.85, Re(650) / Re(550) > 1.03, and Re(750) / Re(550) > 1.05. The second λ / 4 member 22 preferably satisfies at least one selected from 0.65 < Re(400) / Re(550) < 0.80 (preferably, 0.7 < Re(400) / Re(550) < 0.75), 1.0 < Re(650) / Re(550) < 1.25 (preferably, 1.05 < Re(650) / Re(550) < 1.20), and 1.05 < Re(750) / Re(550) < 1.40 (preferably, 1.08 < Re(750) / Re(550) < 1.36), more preferably satisfies at least two, and even more preferably satisfies all of them.
[0036] The second λ / 4 member 22 preferably exhibits a refractive index characteristic of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the second λ / 4 member 22 is preferably 0.9 to 3, more preferably 0.9 to 2.5, even more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.
[0037] The second λ / 4 member 22 is formed of any suitable material that can satisfy the above characteristics. The second λ / 4 member 22 can be, for example, a stretched film of a resin film or an alignment cured layer of a liquid crystal compound. For the second λ / 4 member 22 constituted by the alignment cured layer of the liquid crystal compound, the same description as that of the first λ / 4 member 20 can be applied.
[0038] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cyclic olefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination. Examples of the combination method include blending and copolymerization. When the phase difference member exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) can be suitably used.
[0039] Any suitable polycarbonate-based resin can be used as the polycarbonate-based resin. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diol, alicyclic dimethanol, di-, tri- or polyethylene glycol, and alkylene glycol or spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for phase difference members and methods for forming phase difference members are described, for example, in JP-A-2014-10291, JP-A-2014-26266, JP-A-2015-212816, JP-A-2015-212817, and JP-A-2015-212818, and the descriptions in these publications are incorporated herein by reference.
[0040] The thickness of the second λ / 4 member 22 is preferably 100 μm or less. Specifically, the thickness of the second λ / 4 member 22 made of a stretched resin film is, for example, 10 μm to 100 μm, preferably 10 μm to 70 μm, more preferably 10 μm to 60 μm, and even more preferably 20 μm to 50 μm.
[0041] The first λ / 4 member 20 and the second λ / 4 member 22 may be members having the same configuration (material, thickness, optical properties, etc.) or may be members having different configurations.
[0042] In the display system 2, for example, from the viewpoint of improving visibility, a high degree of adjustment may be required between the retardation value of the first λ / 4 member 20 and the retardation value of the second λ / 4 member 22. For example, the absolute value of the difference between the in-plane retardation (a) of the first λ / 4 member 20 and the in-plane retardation (b) of the second λ / 4 member 22 is, for example, 3.5 nm or less, preferably 3.0 nm or less, more preferably 2.5 nm or less, even more preferably 2.0 nm or less, particularly preferably 1.5 nm or less, and most preferably 1.0 nm or less. (a) and (b) are, for example, values of Re(590).
[0043] For example, it is preferable that the in-plane retardation (a) of the first λ / 4 component 20 and the in-plane retardation (b) of the second λ / 4 component 22 satisfy the following formula (I). ((a)-(b)) / ((a)+(b) / 2)≦0.02···(I) More preferably, ((a)-(b)) / ((a)+(b) / 2)≦0.015, and even more preferably, ((a)-(b)) / ((a)+(b) / 2)≦0.01.
[0044] The reflective polarizing member can transmit polarized light (typically, linearly polarized light) parallel to its transmission axis while maintaining its polarization state, and can reflect light in other polarization states. The orthogonal transmittance (Tc) of the reflective polarizing member can be, for example, 0.01% to 3%. The single transmittance (Ts) of the reflective polarizing member can be, for example, 43% to 49%, preferably 45% to 47%. The polarization degree (P) of the reflective polarizing member can be, for example, 92% to 99.99%. The reflective polarizing member is typically composed of a film (sometimes referred to as a reflective polarizing film) having a multilayer structure. Commercially available reflective polarizing films include, for example, 3M's product names "DBEF" and "APF" and Nitto Denko's product name "APCF".
[0045] As described above, the first λ / 4 member 20 may be provided integrally with a polarizing member that may be included in the display element 12. In this case, it is preferable to form an optical laminate in which the polarizing member that may be included in the display element 12 and the first λ / 4 member 20 are integrated.
[0046] [Optical laminate] 2 is a schematic cross-sectional view showing a schematic configuration of an optical laminate according to one embodiment of the present invention. The optical laminate 1 has a polarizing member 13 that can be included in a display element 12, and a first retardation member 21 arranged on one side (the front side, the upper side in FIG. 2) of the polarizing member 13.
[0047] The polarizing member 13 includes at least a polarizing film 13a. In the example shown in FIG. 2, the polarizing member 13 includes a protective layer 13b in addition to the polarizing film 13a. The polarizing member 13 has a laminated structure of the polarizing film 13a and the protective layer 13b. The polarizing film 13a and the protective layer 13b are laminated, for example, via an adhesive layer (not shown). In this case, the polarizing member 13 includes the polarizing film 13a, the adhesive layer, and the protective layer 13b in this order. In the example shown in FIG. 2, the protective layer 13b is provided only on one side of the polarizing film 13a, but it may be provided on both sides, for example.
[0048] The polarizing film 13a is typically an absorptive polarizing film and may be made of a resin film containing a dichroic material. The thickness of the polarizing film 13a is, for example, 1 μm or more and 20 μm or less, and may be 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, or 8 μm or less. The thickness of the polarizing member 13 is, for example, 10 μm or more and may be 20 μm or more. The thickness of the polarizing member 13 is, for example, 100 μm or less and may be 80 μm or less.
[0049] The absorptive polarizing film may be prepared from a single layer of resin film, or may be prepared using a laminate of two or more layers.
[0050] When preparing from a single-layer resin film, for example, an absorptive polarizing film can be obtained by subjecting a hydrophilic polymer film such as a polyvinyl alcohol (PVA)-based film, a partially formalized PVA-based film, or an ethylene-vinyl acetate copolymer-based partially saponified film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, a stretching treatment, etc. Among them, an absorptive polarizing film obtained by dyeing a PVA-based film with iodine and uniaxially stretching it is preferable.
[0051] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while the dyeing is being carried out. Alternatively, the stretching may be followed by dyeing. If necessary, the PVA film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.
[0052] Examples of the laminate produced using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into an absorptive polarizing film. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of polyvinyl alcohol molecules and the decrease in the orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the absorptive polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through drying shrinkage treatment.The obtained laminate of resin substrate / absorptive polarizing film may be used as it is (i.e., the resin substrate may be used as a protective layer for the absorptive polarizing film), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / absorptive polarizing film laminate after peeling the resin substrate from the laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such an absorptive polarizing film are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0053] The crossed transmittance (Tc) of the polarizing member (absorptive polarizing film) is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the polarizing member (absorptive polarizing film) is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The degree of polarization (P) of the polarizing member (absorptive polarizing film) is, for example, 99.0% to 99.997%, and preferably 99.9% or more.
[0054] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0055] The protective layer 13b that can be included in the polarizing member 13 can be composed of, for example, any appropriate film. Examples of materials that are the main components of the film that constitutes the protective layer include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other resins. Here, (meth)acrylic refers to acrylic and / or methacrylic.
[0056] When the protective layer 13b is made of a film, the thickness is preferably 5 μm to 80 μm, more preferably 10 μm to 50 μm, and further preferably 15 μm to 40 μm.
[0057] The protective layer 13b that can be included in the polarizing member 13 can also be composed of, for example, another phase difference member having any appropriate refractive index characteristics. In the example shown in Fig. 2, the optical laminate 1 has a second phase difference member 13b disposed between the polarizing film 13a and the first phase difference member 21. The second phase difference member 13b is laminated on the polarizing film 13a via, for example, an adhesive layer (not shown).
[0058] The second phase difference member 13b is provided from the viewpoint of compensating for the deviation of the optical axis relationship between the polarizing member 13 and the reflective polarizing member caused by the change in the viewing angle, for example. In this case, the second phase difference member 13b may include at least one optical compensation layer having a slow axis. The optical compensation layer having a slow axis (hereinafter referred to as the first optical compensation layer) may be arranged so that its slow axis is approximately perpendicular or approximately parallel to the absorption axis of the polarizing film 13a. With this configuration, the light emitted from the display element 12 as the first linearly polarized light can pass through the second phase difference member 13b without substantially changing its polarization state. In this specification, the term "optical compensation layer having a slow axis" refers to an optical compensation layer having Re(550) of 10 nm or more.
[0059] In one embodiment, the first optical compensation layer is a layer (so-called negative B plate) whose refractive index characteristics show the relationship of nx>ny>nz. In this case, the second phase difference member 13b preferably includes a second optical compensation layer in addition to the first optical compensation layer. The second optical compensation layer is, for example, a layer (so-called positive B plate) whose refractive index characteristics show the relationship of nz>nx>ny, and the second phase difference member 13b may have a laminated structure in which the first optical compensation layer and the second optical compensation layer are laminated in this order from the polarizing film 13a side. The first optical compensation layer and the second optical compensation layer may be typically laminated via an adhesive layer. Specifically, the first optical compensation layer, the adhesive layer, and the second optical compensation layer may be included in this order. The slow axis of the first optical compensation layer and the slow axis of the second optical compensation layer may both be arranged to be approximately perpendicular to the absorption axis of the polarizing film 13a.
[0060] In another embodiment, the first optical compensation layer is a member (so-called Z plate) whose refractive index characteristics show the relationship of nx>nz>ny. Specifically, the second phase difference member 32 can be composed of a Z plate. In this case, the slow axis of the optical compensation layer can be arranged to be approximately perpendicular or approximately parallel to the absorption axis of the polarizing member 13.
[0061] The thickness of the second phase difference member 13b varies depending on the configuration, but is, for example, 200 μm or less, preferably 5 μm to 170 μm, and more preferably 10 μm to 150 μm.
[0062] The in-plane retardation Re(550) of the negative B plate is, for example, 60 nm to 190 nm, preferably 80 nm to 170 nm, and more preferably 100 nm to 150 nm. The thickness direction retardation Rth(550) of the negative B plate is, for example, 60 nm to 200 nm, preferably 80 nm to 180 nm, and more preferably 100 nm to 160 nm. The Nz coefficient of the negative B plate is, for example, 1.1 to 3.0, and preferably 1.1 to 2.7. The negative B plate may exhibit reverse wavelength dispersion characteristics, may exhibit positive wavelength dispersion characteristics, or may exhibit flat wavelength dispersion characteristics.
[0063] The negative B plate may be made of any suitable material that can satisfy the above characteristics. The negative B plate is made of, for example, a stretched resin film. Examples of resins contained in the resin film include cycloolefin resins (e.g., norbornene resins), polycarbonate resins, cellulose resins, polyvinyl alcohol resins, polysulfone resins, and the like. Such resins can be used alone or in combination. The resin film preferably contains a norbornene resin and / or a cellulose resin. Details of these resins and the stretching method of the resin film are described, for example, in JP 2018-205485 A. The description of this publication is incorporated herein by reference.
[0064] The thickness of the negative B plate is, for example, 10 μm to 80 μm, or, for example, 15 μm to 60 μm.
[0065] The positive B plate has an in-plane retardation Re(550) of, for example, 10 nm to 60 nm, preferably 15 nm to 55 nm, and more preferably 20 nm to 45 nm. The positive B plate has a thickness direction retardation Rth(550) of, for example, -250 nm to -10 nm, preferably -200 nm to -20 nm, and more preferably -150 nm to -60 nm. The positive B plate has an Nz coefficient of, for example, -4.0 to -1.0, preferably -3.5 to -1.5, and more preferably -3.0 to -2.0. The positive B plate may exhibit a reverse wavelength dispersion characteristic, a positive wavelength dispersion characteristic, or a flat wavelength dispersion characteristic.
[0066] The positive B plate may be made of any suitable material that can satisfy the above characteristics. The positive B plate may be made of, for example, a stretched film of a resin film. Examples of resins that constitute the positive B plate include thermoplastic resins, and polymers that exhibit negative intrinsic birefringence may be preferably used. A polymer that exhibits negative intrinsic birefringence and a polymer that exhibits positive intrinsic birefringence may be used in combination. By using a polymer that exhibits negative intrinsic birefringence, a retardation member that exhibits a refractive index characteristic of nz>nx>ny and has excellent uniformity in the slow axis direction can be easily obtained. Here, "exhibiting negative intrinsic birefringence" means that when a polymer is oriented by stretching or the like, the refractive index in the stretching direction becomes relatively small. In other words, it means that the refractive index in the direction perpendicular to the stretching direction becomes large.
[0067] Examples of polymers that exhibit negative intrinsic birefringence include polymers in which a chemical bond or functional group with large polarization anisotropy, such as an aromatic ring or a carbonyl group, is introduced into the side chain.Specific examples include acrylic resins, styrene resins, maleimide resins, and fumaric acid ester resins, and preferably styrene resins and fumaric acid ester resins.These can be used alone or in combination of two or more.
[0068] Preferred examples of the styrene-based resin include styrene-maleic anhydride copolymers, styrene-acrylonitrile copolymers, styrene-(meth)acrylate copolymers, styrene-maleimide copolymers, vinyl ester-maleimide copolymers, and olefin-maleimide copolymers.
[0069] As the fumaric acid ester-based resin, preferably, a fumaric acid ester-(meth)acrylate copolymer is used.
[0070] A preferred example of the polymer exhibiting the negative intrinsic birefringence is a polymer having a repeating unit represented by the following general formula (I). Such a polymer exhibits a higher negative birefringence and can have excellent heat resistance and mechanical strength. Such a polymer can be obtained, for example, by using an N-phenyl-substituted maleimide in which a phenyl group having a substituent at least at the ortho position is introduced as the N-substituent of the maleimide monomer as the starting material. [ka] In the above general formula (I), R1 to R5 each independently represent a hydrogen atom, a halogen atom, a carboxylic acid, a carboxylate, a hydroxyl group, a nitro group, or a linear or branched alkyl or alkoxy group having 1 to 8 carbon atoms (provided that R1 and R5 are not simultaneously hydrogen atoms), R6 and R7 represent a hydrogen atom, or a linear or branched alkyl or alkoxy group having 1 to 8 carbon atoms, and n represents an integer of 2 or greater.
[0071] The positive B plate can be obtained by stretching a resin film containing the above-mentioned resin under any appropriate stretching conditions.
[0072] The thickness of the positive B plate is, for example, 1 μm to 30 μm, preferably 2 μm to 20 μm, and more preferably 3 μm to 10 μm.
[0073] The in-plane retardation Re(550) of the Z-plate is, for example, 200 nm to 350 nm, preferably 230 nm to 320 nm, and more preferably 250 nm to 300 nm. The Nz coefficient of the Z-plate is, for example, 0.2 to 0.8, preferably 0.3 to 0.7, and more preferably 0.4 to 0.6. The Z-plate may exhibit reverse wavelength dispersion characteristics, may exhibit positive wavelength dispersion characteristics, or may exhibit flat wavelength dispersion characteristics.
[0074] The Z-plate may be made of any suitable material that satisfies the above characteristics. The Z-plate may be made of, for example, a resin film. Examples of the resin that constitutes the Z-plate include polyarylate-based resins, polyamide-based resins, polyimide-based resins, polyester-based resins, polyaryletherketone-based resins, polyamideimide-based resins, polyesterimide-based resins, polyvinyl alcohol-based resins, polyfumaric acid ester-based resins, polyethersulfone-based resins, polysulfone-based resins, cycloolefin-based resins, polycarbonate-based resins, cellulose-based resins, and polyurethane-based resins. Such resins may be used alone or in combination.
[0075] The resin constituting the Z-plate is preferably a cycloolefin resin, more preferably a norbornene resin. A specific example of the norbornene resin is the "cycloolefin resin obtained by hydrogenating a ring-opening polymer of a norbornene monomer" described in JP-A-2006-208925.
[0076] The Z-plate can be produced, for example, by laminating a high shrinkage film (e.g., polypropylene film) to both sides of a polymer film mainly composed of the above-mentioned resin, and then heat-stretching the film by a longitudinal uniaxial stretching method using a roll stretching machine. The high shrinkage film is used to impart a shrinkage force in a direction perpendicular to the stretching direction during heat-stretching, thereby increasing the refractive index (nz) of the Z-plate in the thickness direction. There are no particular limitations on the method for laminating the high shrinkage film to both sides of the polymer film, but examples of the method include a method in which an acrylic adhesive layer having an acrylic polymer as a base polymer is provided between the polymer film and the high shrinkage film to bond them together.
[0077] The thickness of the Z plate is, for example, 20 μm to 200 μm, or, for example, 30 μm to 150 μm.
[0078] The first phase difference member 21 includes at least a first λ / 4 member 20. In the example shown in FIG. 2, the first phase difference member 21 includes another phase difference layer 23 in addition to the first λ / 4 member 20. The other phase difference layer 23 is composed of, for example, a member (so-called positive C plate) whose refractive index characteristics can show the relationship of nz>nx=ny. The first phase difference member 21 has a laminated structure of the first λ / 4 member 20 and the other phase difference layer 23. The first λ / 4 member 20 and the other phase difference layer 23 are laminated, for example, via an adhesive layer not shown. In this case, the first phase difference member 21 includes the first λ / 4 member 20, an adhesive layer, and the other phase difference layer 23. When the other phase difference layer 23 is composed of a positive C plate, it is preferable that the other phase difference layer (positive C plate) 23 is located forward of the first λ / 4 member 20 in the first phase difference member 21 as shown in FIG. 2.
[0079] The thickness direction retardation Rth(550) of the positive C plate is preferably -50nm to -300nm, more preferably -70nm to -250nm, further preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane retardation Re(550) of the positive C plate is, for example, less than 10nm.
[0080] The positive C plate may be formed of any suitable material, but is preferably composed of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of such liquid crystal compounds and methods for forming a positive C plate include the liquid crystal compounds and methods for forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the positive C plate is preferably 0.5 μm to 5 μm.
[0081] A first pressure-sensitive adhesive layer 41 is provided between the polarizing member 13 and the first phase difference member 21. The first pressure-sensitive adhesive layer 41 is disposed adjacent to the first phase difference member 21. The first phase difference member 21 is bonded to the laminated portion including the polarizing member 13 via the first pressure-sensitive adhesive layer 41.
[0082] The optical laminate 1 further has a protective member 30 arranged in front of the first retardation member 21. The protective member 30 is laminated to the first retardation member 21 via a second adhesive layer 42. In the display system 2, typically, a space is formed between the optical laminate 1 and the first lens portion 16. The protective member 30 can be located on the outermost surface of the optical laminate 1, and can protect a member arranged behind it (lower side in FIG. 2).
[0083] The protective member 30 typically includes a substrate. The thickness of the substrate is preferably 5 μm to 80 μm, more preferably 10 μm to 50 μm, and further preferably 15 μm to 40 μm. The substrate may be made of any appropriate film. Examples of materials that are the main components of the film that constitutes the substrate include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic-based, acetate-based, and other resins.
[0084] The protective member 30 preferably has a substrate and a surface treatment layer formed on the substrate. The protective member 30 having the surface treatment layer may be disposed so that the surface treatment layer is located on the front side. Specifically, the surface treatment layer may be located on the outermost surface of the optical laminate 1. The surface treatment layer may have any appropriate function. For example, from the viewpoint of improving visibility, the surface treatment layer preferably has an anti-reflection function. The thickness of the surface treatment layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.
[0085] Although not shown, the optical laminate 1 may have a third phase difference member that may be included in the display element 12. The third phase difference member may be disposed behind the polarizing member 13. The third phase difference member may be laminated, for example, on the polarizing member 13 via an adhesive layer. The third phase difference member may be, for example, a λ / 4 member (hereinafter referred to as a third λ / 4 member). The same explanation as for the second λ / 4 member 22 can be applied to the third λ / 4 member. The angle between the absorption axis of the polarizing member 13 and the slow axis of the third phase difference member (third λ / 4 member) is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. When the display element 12 is an organic EL display, by providing the third λ / 4 member together with the polarizing member 13, problems such as external light reflection and background reflection due to a metal layer that may be included in the organic EL display can be solved. In addition, the problem of reflection due to light leakage from the display element 12 in the display system 2 can be solved.
[0086] In the optical laminate 1, the adhesive layer used for laminating each member (layer) may be formed of an adhesive or a pressure-sensitive adhesive. Specifically, the adhesive layer may be an adhesive layer or a pressure-sensitive adhesive layer. The thickness of the adhesive layer is, for example, 0.01 μm to 60 μm.
[0087] The polarizing film 13a included in the polarizing member 13 tends to shrink easily when heated, etc. In particular, it tends to shrink easily along the absorption axis direction (for example, the stretching direction in the manufacturing process of the polarizing film 13a). The linear expansion coefficient of the absorption axis direction of the polarizing member 13 at 25° C. to 65° C. is, for example, −5.0×10 -4 / ℃ or more -1.0×10 -4 / ℃ or less, -1.5×10 -4 / ℃ or less, -1.9 × 10 -4 / ℃ or less, -2.0×10 -4 The linear expansion coefficient of the polarizing member 13 in the transmission axis direction at 25° C. to 65° C. may be, for example, −3.0×10 -4 / ℃ or more -0.2×10 -4 / ℃ or less, -0.5×10 -4 / °C or less. Since the polarizing member 13 may be included in the display element 12, it is easily affected by the heat of the display element 12. The absorption axis direction of the polarizing member 13 corresponds to the absorption axis direction of the polarizing film 13a, and the transmission axis direction of the polarizing member 13 corresponds to the transmission axis direction of the polarizing film 13a. The absorption axis direction of the polarizing film 13a and the transmission axis direction of the polarizing film 13a may be perpendicular to each other.
[0088] When the optical laminate 1 is formed, the linear expansion coefficient of the first phase difference member 21 in the absorption axis direction of the polarizing member 13 at 25° C. to 65° C. is, for example, 0.1×10 -4 / ℃ or more 1.5×10 -4 / ℃ or less, 0.5×10 -4 / ℃ or more, and -4 / ℃ or more, and -4 When the optical laminate 1 is formed, the linear expansion coefficient of the first phase difference member 21 in the transmission axis direction of the polarizing member 13 at 25° C. to 65° C. is, for example, 0.1×10 -4 / ℃ or more 1.5×10 -4 / ℃ or less, 0.2×10 -4 / °C or more.
[0089] The absolute value of the difference between the linear expansion coefficient of the polarizing member 13 in the absorption axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member 13 in the absorption axis direction of the first phase difference member 21 in the optical laminate 1 at 25° C. to 65° C. is, for example, 2.5×10 -4 / ℃ or more 5.0×10 -4 / ℃ or less, 2.5×10 -4 / ℃ or more 4.5×10 -4 / ° C. or less. The absolute value of the difference between the linear expansion coefficient of the polarizing member 13 in the transmission axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member 13 in the transmission axis direction of the first retardation member 21 in the optical laminate 1 at 25° C. to 65° C. may be, for example, 0.4×10 -4 / ℃ or more 4.0×10 -4 / ℃ or less, 0.5×10 -4 / ℃ or more 3.0×10 -4 / °C or less, and may be 1.0 x 10 -4 / ℃ or more 2.5×10-4 / °C or less, and may be 1.1 x 10 -4 / ℃ or more 2.0×10 -4 / ° C. or less. The ratio of the absolute value of the difference between the linear expansion coefficient at 25° C. to 65° C. in the absorption axis direction of the polarizing member 13 and the linear expansion coefficient at 25° C. to 65° C. in the absorption axis direction of the polarizing member 13 of the first phase difference member 21 when made into the optical laminate 1 to the absolute value of the difference between the linear expansion coefficient at 25° C. to 65° C. in the transmission axis direction of the polarizing member 13 and the linear expansion coefficient at 25° C. to 65° C. in the transmission axis direction of the polarizing member 13 of the first phase difference member 21 when made into the optical laminate 1 to the absolute value of the difference between the linear expansion coefficient at 25° C. to 65° C. in the transmission axis direction of the polarizing member 13 of the first phase difference member 21 when made into the optical laminate 1 is, for example, 0.3 to 0.8, and may be 0.6 or less.
[0090] The members integrated with the polarizing member 13 may be affected by the shrinkage of the polarizing member 13. As described above, in the display system 2, while the retardation value of the first λ / 4 member 20 and the retardation value of the second λ / 4 member 22 may require high-level adjustment, the first λ / 4 member 20 may be affected by the shrinkage of the polarizing member 13 and the retardation value may change. By providing the first adhesive layer 41 between the polarizing member 13 and the first λ / 4 member 20 (first retardation member 21), the influence of the shrinkage of the polarizing member 13 on the first λ / 4 member 20 can be reduced (for example, dimensional change can be suppressed), and the change in the retardation value of the first λ / 4 member 20 can be suppressed.
[0091] The first adhesive layer 41 may be made of any suitable adhesive. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more kinds. An acrylic resin is preferably used as the base resin. Specifically, the adhesive layer is preferably made of an acrylic adhesive.
[0092] The elastic modulus of first pressure-sensitive adhesive layer 41 at 85° C. is preferably 0.07 MPa to 0.5 MPa, and more preferably 0.1 MPa to 0.3 MPa.
[0093] The thickness of the first pressure-sensitive adhesive layer 41 is preferably 3 μm or more. On the other hand, the thickness of the first pressure-sensitive adhesive layer 41 is preferably 25 μm or less, and may be 20 μm or less, 15 μm or less, 10 μm or less, or 7 μm or less. With such a thickness, excellent smoothness can be obtained.
[0094] The optical laminate 1 may be formed in a sheet shape. Typically, the planar shape of the optical laminate 1 may be a rectangle, a rectangle with rounded corners, or the like. In one embodiment, the long side of the optical laminate 1 is aligned with the absorption axis of the polarizing member 13, and the short side of the optical laminate 1 is aligned with the transmission axis of the polarizing member 13. EXAMPLES
[0095] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.
[0096] (1) Thickness The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (2) Phase difference value The phase difference value at a predetermined wavelength was measured at 23° C. using a phase difference / ellipsoidal polarization measuring device (manufactured by Oji Scientific Instruments, product names "KOBRA-HBR" and "KOBRA-HBPR"). (3) Single transmittance and polarization degree of the polarizing element The single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc of the polarizing element were measured using a spectrophotometer (Otsuka Electronics Co., Ltd., "LPF-200"). These Ts, Tp, and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. The degree of polarization of the polarizing element was calculated from the obtained Tp and Tc using the following formula. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100 (4) Linear expansion coefficient Using "TMA Q400" (manufactured by TA-instrument), the linear expansion coefficient of the measurement sample was measured at temperatures from 25°C to 65°C in a tensile mode under a nitrogen atmosphere (nitrogen gas flow rate: 50 ml / min, relative humidity: 0%) and an applied load of 19.6 mN. Specifically, both ends of a rectangular measurement sample cut to a size of 4 mm wide and 30 mm long were set 16 mm apart on the probe of the "TMA Q400". The sample was then heated from 25°C to 65°C at a rate of 0.33°C / min while measuring the dimensional change. From the obtained data, the slope of the dimensional change from 25°C to 65°C (linear expansion coefficient) was calculated. The length direction of the measurement sample corresponded to the direction to be measured. (5) Elastic modulus The measurement object (e.g., a pressure-sensitive adhesive layer) was molded to a thickness of 2 mm by lamination. This molded product was punched into a disk shape with a diameter of 7.9 mm to prepare a test piece. This test piece was sandwiched between parallel plates, and dynamic viscoelasticity measurement was performed under the following conditions using a dynamic viscoelasticity measuring device (Rheometric Scientific's "Advanced Rheometric Expansion System (ARES)") to determine the storage modulus at 85°C. (Measurement conditions) Deformation mode: Torsion ·Measurement frequency: 1Hz ·Measurement temperature: -40℃~+150℃ Heating rate: 5℃ / min
[0097] [Production Example 1] (Preparation of absorptive polarizing film) As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating liquid) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Mitsubishi Chemical Corporation, product name "GOHSENEX Z410") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained absorptive polarizing film would be the desired value (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at about 90° C., it was brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 5.2%. In this manner, an absorptive polarizing film having a thickness of about 5 μm was formed on the resin substrate.
[0098] (Preparation of positive B plate) A positive B plate having refractive index characteristics of nz>nx>ny was prepared as follows. In an autoclave equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 48 parts by weight of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "Metolose 60SH-50"), 15601 parts by weight of distilled water, 8161 parts by weight of diisopropyl fumarate, 240 parts by weight of 3-ethyl-3-oxetanylmethyl acrylate and 45 parts by weight of t-butyl peroxypivalate as a polymerization initiator were placed, and after nitrogen bubbling for 1 hour, the mixture was stirred and held at 49°C for 24 hours to carry out radical suspension polymerization. The mixture was then cooled to room temperature, and the suspension containing the produced polymer particles was centrifuged. The obtained polymer was washed twice with distilled water and twice with methanol, and then dried under reduced pressure to obtain a fumarate ester resin. The obtained fumaric acid ester resin was dissolved in a toluene-methyl ethyl ketone mixed solution (toluene / methyl ethyl ketone 50% / 50% by weight) to obtain a solution with a solid content of 20% by weight. Furthermore, 5 parts by weight of tributyl trimellitate as a plasticizer was added to 100 parts by weight of the fumaric acid ester resin to obtain a dope. A biaxially stretched film of polyester (polyethylene terephthalate / isophthalate copolymer) with a thickness of 75 μm and a width of 1350 mm was used as the support film. The roll of the support film was set in the unwinding section of the film-forming device, and while the support film was unwound and transported downstream, the obtained dope was applied onto the support film so that the film thickness after drying would be 20 μm, and then dried at 140 ° C to obtain a laminate. The obtained laminate was set in the unwinding section of a stretching device, and while the laminate was unwound and conveyed downstream, it was subjected to free-end uniaxial stretching in a stretching furnace at a temperature of 140° C. The support film was peeled off from the stretched laminate to obtain a positive B plate (thickness 5 μm, Re(550): 35 nm, Rth(550): −85 nm).
[0099] (Preparation of negative B plate) As a negative B plate, a stretched film of a cycloolefin resin film (manufactured by Zeon Corporation, product name: ZT12, thickness: 18 μm, Re(550): 116 nm, Rth(550): 139 nm) was prepared.
[0100] (Preparation of second phase difference member) The positive B plate was attached to one side of the negative B plate via a 2 μm thick curable adhesive layer to obtain a second retardation member. In the second retardation member, the angle between the slow axis of the negative B plate and the slow axis of the positive B plate was 0°.
[0101] (Preparation of polarizing member) The obtained second phase difference member was attached to the surface of the obtained absorptive polarizing film (the surface opposite to the resin substrate) via a 2 μm-thick curable adhesive layer. At this time, the attachment was performed so that the absorption axis of the absorptive polarizing film was perpendicular to the slow axes of the negative B plate and the positive B plate. The second phase difference member was attached so that the negative B plate was located on the absorptive polarizing film side. Next, the resin substrate was peeled off. In this way, a polarizing member having a second phase difference member / absorptive polarizing film configuration was obtained. The single transmittance (Ts) of the polarizing member was 43.4%, and the polarization degree was 99.993%. The linear expansion coefficient of the polarizing member in the absorption axis direction (first direction) was -2.60×10 -4 / °C, and the linear expansion coefficient in the transmission axis direction (second direction) is -1.25×10 -4 / ℃.
[0102] [Production Example 2] (Formation of λ / 4 components) 55 parts of a compound represented by the following formula (I), 25 parts of a compound represented by the following formula (II), and 20 parts of a compound represented by the following formula (III) were added to 400 parts of cyclopentanone (CPN), and then heated to 60°C and stirred to dissolve. After dissolution was confirmed, the mixture was returned to room temperature, and 3 parts of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts of p-methoxyphenol (MEHQ) were added and further stirred to obtain a solution. The solution was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. The polyimide solution for the alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, dried at 100°C for 10 minutes, and then baked at 200°C for 60 minutes to obtain a coating film. The obtained coating film was subjected to a rubbing treatment using a commercially available rubbing device to form an alignment film. The polymerizable composition obtained above was applied to the alignment film (substrate) by spin coating, and dried at 100°C for 2 minutes. The obtained coating film was cooled to room temperature, and then illuminated with a high-pressure mercury lamp at 30 mW / cm. 2 The layer was irradiated with ultraviolet light at an intensity of 100 nm for 30 seconds to obtain a 3 μm thick liquid crystal alignment layer. The obtained liquid crystal alignment layer had an in-plane retardation Re(550) of 130 nm, a Re(450) / Re(550) of 0.851, and showed reverse dispersion wavelength characteristics.
[0103] [ka] [ka]
[0104] (Positive C-plate formation) A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (1) (the numbers 65 and 35 in the formula indicate the mole percent of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. The coating solution was then applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a positive C plate with a thickness of 4 μm and an Rth(550) of -100 nm on the substrate. [ka]
[0105] (Preparation of first phase difference member) The positive C plate was attached to the λ / 4 member (liquid crystal alignment solidified layer) via a 2 μm thick curable adhesive layer, and then the base material was removed to obtain a first phase difference member. The linear expansion coefficient of the obtained first phase difference member in the first direction was 1.00×10 -4 / °C, and the linear expansion coefficient in the second direction is 0.69 x 10 -4 / ° C. The first direction is the absorption axis direction of the polarizing member (absorptive polarizing film) when made into an optical laminate, and the second direction is the absorption axis direction of the polarizing member (absorptive polarizing film) when made into an optical laminate.
[0106] [Production Example 3] (Creating protective materials) The following hard coat layer forming material was applied to an acrylic film (thickness 40 μm) having a lactone ring structure and heated at 90° C. for 1 minute. After heating, the coating layer was irradiated with a high-pressure mercury lamp with an integrated light intensity of 300 mJ / cm. 2 The coating layer was cured by irradiation with ultraviolet light of 1000 .mu.m to prepare an acrylic film (thickness 44 .mu.m) on which a hard coat layer with a thickness of 4 .mu.m was formed. Next, the following coating solution A for forming an anti-reflection layer was applied onto the hard coat layer using a wire bar, and the applied coating solution was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was then irradiated with a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm2. 2 The coating was cured by irradiation with ultraviolet light of 1500 nm to form an antireflection layer A having a thickness of 140 nm. Next, the following coating solution B for forming an antireflection layer was applied onto the antireflection layer A using a wire bar, and the applied coating solution was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was irradiated with a high-pressure mercury lamp with an integrated light amount of 300 mJ / cm 2 The coating was cured by irradiation with ultraviolet light of 1000 ohms to form an antireflection layer B having a thickness of 105 nm. In this way, a protective member (thickness 44 μm) was obtained. The linear expansion coefficient of the obtained protective member in the first direction was 0.52×10 -4 / °C, and the linear expansion coefficient in the second direction is 0.59 x 10 -4 / ℃.
[0107] (Hard Coat Layer Forming Material) A hard coat layer forming material was prepared by mixing 50 parts of a urethane acrylic oligomer (manufactured by Shin-Nakamura Chemical Co., Ltd., "NK Oligo UA-53H"), 30 parts of a multifunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300"), 20 parts of 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.), 1 part of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100") and 3 parts of a photopolymerization initiator (manufactured by Ciba Japan, "Irgacure 907") and diluting with methyl isobutyl ketone to a solids concentration of 50%.
[0108] (Anti-reflection layer forming coating solution A) 100 parts by weight of a multifunctional acrylate (manufactured by Arakawa Chemical Industries, Ltd., product name "Opstar KZ6728", solid content 20% by weight), 3 parts by weight of a leveling agent (manufactured by DIC Corporation, "GRANDIC PC4100"), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907", solid content 100% by weight) were mixed. The mixture was diluted with butyl acetate as a diluting solvent to a solid content of 12% by weight, and the mixture was stirred to prepare coating solution A for forming an anti-reflection layer.
[0109] (Anti-reflection layer forming coating solution B) 100 parts by weight of a polyfunctional acrylate mainly composed of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 150 parts by weight of hollow nanosilica particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., trade name "Surulia 5320", solid content 20% by weight, weight average particle diameter 75 nm), 50 parts by weight of solid nanosilica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle diameter 10 nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907", solid content 100% by weight) were mixed. To the mixture was added a mixed solvent of TBA (tertiary butyl alcohol), MIBK (methyl isobutyl ketone) and PMA (propylene glycol monomethyl ether acetate) in a weight ratio of 60:25:15 as a dilution solvent until the total solids content was 4% by weight, and the mixture was stirred to prepare coating solution B for forming an anti-reflection layer.
[0110] [Production Example 4] (Formation of Adhesive Layer A) A monomer mixture containing 92 parts by weight of butyl acrylate, 2.9 parts by weight of acrylic acid, 0.1 parts by weight of 2-hydroxyethyl acrylate, and 5 parts by weight of N-acryloylmorpholine was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 200 parts by weight of ethyl acetate per 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at around 55°C, and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution with a weight average molecular weight (Mw) of 1.78 million. The acrylic polymer solution was applied to the substrate film, and the resulting coating film on the substrate film was dried in an oven to form a pressure-sensitive adhesive layer A having a thickness of 5 μm (elastic modulus: 0.13 MPa).
[0111] [Production Example 5] (Formation of Adhesive Layer B) A monomer mixture containing 94.9 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.3 parts by weight of dibenzoyl peroxide as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of this monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere in the flask with nitrogen. The liquid temperature in the flask was kept at 60°C and a polymerization reaction was carried out for 7 hours. Next, ethyl acetate was added to the resulting reaction liquid to adjust the solid concentration to 30% by weight, and a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.2 million was prepared. An acrylic adhesive was prepared by blending 100 parts by weight of the solid content of the obtained acrylic polymer solution with 0.6 parts by weight of a trimethylolpropane / tolylene diisocyanate adduct (product name: Coronate L, manufactured by Tosoh Corporation) and 0.075 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.). The obtained acrylic adhesive was applied to a substrate film, and the resulting coating film on the substrate film was dried in an oven to form adhesive layers B (elastic modulus: 0.10 MPa) having thicknesses of 23 μm and 15 μm.
[0112] [Production Example 6] (Fabrication of λ / 4 components) Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux condenser controlled at 100° C. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane 29.60 parts by mass (0.046 mol), isosorbide (ISB) 29.21 parts by mass (0.200 mol), spiroglycol (SPG) 42.28 parts by mass (0.139 mol), diphenyl carbonate (DPC) 63.77 parts by mass (0.298 mol), and calcium acetate monohydrate 1.19×10 as a catalyst. -2 Part of mass (6.78×10 -5 mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was reduced and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure to 0.2 kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets.
[0113] The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a long resin film with a thickness of 135 μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a chill roll (setting temperature: 120 to 130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a stretched film with a thickness of 47 μm. The Re(550) of the obtained stretched film was 143 nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12. The linear expansion coefficient of the obtained stretched film in the direction at an angle of 45° to the slow axis direction was 0.6×10 -4 / ℃.
[0114] [Example 1] The first phase difference member obtained in Production Example 2 was attached to the positive B plate side of the second phase difference member of the polarizing member obtained in Production Example 1 via the 5 μm thick adhesive layer A obtained in Production Example 4. At this time, the polarizing member was attached so that the angle between the absorption axis of the polarizing member and the slow axis of the λ / 4 member of the first phase difference member was 45°. In addition, the λ / 4 member of the first phase difference member was attached to the polarizing member side. Next, the protective member obtained in Production Example 3 was attached to the positive C plate side of the first retardation member via the pressure-sensitive adhesive layer B having a thickness of 15 μm obtained in Production Example 5. At this time, the acrylic film of the protective member was attached to the polarizing member side. In this way, an optical laminate was obtained.
[0115] [Example 2] An optical laminate was obtained in the same manner as in Example 1, except that the pressure-sensitive adhesive layer B having a thickness of 23 μm obtained in Production Example 5 was used for laminating the second retardation member and the first retardation member.
[0116] [Example 3] An optical laminate was obtained in the same manner as in Example 1, except that the pressure-sensitive adhesive layer B having a thickness of 15 μm obtained in Production Example 5 was used for laminating the second retardation member and the first retardation member.
[0117] [Comparative Example 1] An optical laminate was obtained in the same manner as in Example 1, except that the second retardation member and the first retardation member were bonded together via a curable adhesive layer having a thickness of 2 μm.
[0118] <Evaluation> The retardation change was evaluated for each of the Examples and Comparative Examples as follows. The evaluation results are summarized in Table 1.
[0119] (Method of evaluating phase difference change) A 40 μm-thick acrylic film having a lactone ring structure was attached as a protective layer to the surface of the absorptive polarizing film of the obtained optical laminate via a UV-curable adhesive. Specifically, the curable adhesive was applied to a thickness of 2 μm, and the two were attached using a rolling machine. Then, the adhesive was cured by irradiating it with UV light from the acrylic film side. Thus, a measurement sample to be subjected to a heating test was obtained. The obtained measurement sample was subjected to a heating test under the following conditions, and the retardation value (in-plane retardation) before and after the heating test was measured, and the retardation change was calculated. Using the above retardation / ellipsoidal polarization measuring device, light with a wavelength of 550 nm was incident on the polarizing member side of the optical laminate at 23° C., and the in-plane retardation Re(550) was measured. The in-plane retardation of the optical laminate may correspond to the in-plane retardation of a λ / 4 member. The retardation change shown in 1 is a value calculated from the formula: retardation value after heating test−retardation value before heating test. Heating test 1: Heated for 168 hours at 65°C and 90% relative humidity Heating test 2: Heat cycle test Heating test 3: Heated for 120 hours at a temperature of 85°C and a relative humidity of 85% In the heat cycle test, the sample was placed in an environment with a temperature of 85° C. and a relative humidity of 0% for 30 minutes, and then in an environment with a temperature of −40° C. and a relative humidity of 0% for 30 minutes, and this operation was repeated 100 times in total.
[0120] [Table 1]
[0121] Compared with Comparative Example 1, in each of the Examples, the change in retardation due to the heating test was significantly smaller.
[0122] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that provides the same effect, or a configuration that can achieve the same purpose. [Industrial Applicability]
[0123] A display system according to an embodiment of the present invention can be used in a display device such as VR goggles. [Explanation of symbols]
[0124] 1 optical laminate, 2 display system, 12 display element, 12a display surface, 13 polarizing member, 13a polarizing film, 13b protective layer (second phase difference member), 14 reflective portion (reflective polarizing member), 16 first lens portion, 18 half mirror, 20 first λ / 4 member, 21 first phase difference member, 22 second λ / 4 member, 23 other phase difference layer, 24 second lens portion, 30 protective member, 41 first adhesive layer, 42 second adhesive layer.
Claims
1. A step of passing the light representing the image outputted through the polarizing member through a first λ / 4 member; A step of passing the light having passed through the first λ / 4 member through a half mirror and a first lens portion; A step of passing the light that has passed through the half mirror and the first lens portion through a second λ / 4 member; A step of reflecting the light that has passed through the second λ / 4 member toward the half mirror by a reflective polarizing member; allowing the light reflected by the reflective polarizing member and the half mirror to pass through the reflective polarizing member by the second λ / 4 member; An optical laminate for use in a display method, comprising: a first phase difference member including the polarizing member and the first λ / 4 member; and a pressure-sensitive adhesive layer disposed between the polarizing member and the first phase difference member; The linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. is −1.9×10 -4 / °C or less, the first λ / 4 member is a liquid crystal alignment solidified layer, The pressure-sensitive adhesive layer has an elastic modulus of 0.07 MPa to 0.5 MPa at 85°C. Optical laminate.
2. When the optical laminate is formed, the linear expansion coefficient of the first phase difference member in the absorption axis direction of the polarizing member at 25° C. to 65° C. is 0.6×10 -4 The optical laminate according to claim 1, wherein the temperature is 100° C. or higher.
3. The optical laminate according to claim 1 , wherein the first λ / 4 member has a thickness of 5 μm or less.
4. The optical laminate according to claim 1 , wherein the first retardation member further includes another retardation layer.
5. The absolute value of the difference between the linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. of the first phase difference member when the optical laminate is formed is 2.5×10 -4 The optical laminate according to claim 1, wherein the temperature is 100° C. or higher.
6. The absolute value of the difference between the linear expansion coefficient of the polarizing member in the transmission axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member in the transmission axis direction at 25° C. to 65° C. of the first phase difference member when the optical laminate is formed is 1.1×10 -4 The optical laminate according to claim 1, wherein the temperature is 100° C. or higher.
7. 2. The optical laminate according to claim 1, wherein the ratio of the absolute value of the difference between the linear expansion coefficient at 25°C to 65°C in the absorption axis direction of the polarizing element and the linear expansion coefficient at 25°C to 65°C in the absorption axis direction of the polarizing element of the first phase difference element when made into the optical laminate to the absolute value of the difference between the linear expansion coefficient at 25°C to 65°C in the transmission axis direction of the polarizing element and the linear expansion coefficient at 25°C to 65°C in the transmission axis direction of the polarizing element of the first phase difference element when made into the optical laminate is 0.6 or less.
8. 1. A display system for displaying an image to a user, comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member disposed in front of the display element and configured to reflect light emitted from the display element; a first lens portion disposed on an optical path between the display element and the reflective polarizing member; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member disposed on an optical path between the display element and the half mirror; a second λ / 4 member disposed on an optical path between the half mirror and the reflective polarizing member; The polarizing member includes a first phase difference member including the first λ / 4 member, and an optical laminate having a pressure-sensitive adhesive layer disposed between the polarizing member and the first phase difference member, The linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. is −1.9×10 -4 / °C or less, the first λ / 4 member is a liquid crystal alignment solidified layer, The pressure-sensitive adhesive layer has an elastic modulus of 0.07 MPa to 0.5 MPa at 85°C. Display system.
9. When the optical laminate is formed, the linear expansion coefficient of the first phase difference member in the absorption axis direction of the polarizing member at 25° C. to 65° C. is 0.6×10 -4 9. The display system of claim 8, wherein the temperature is 100° C. or higher.
10. The display system of claim 8 , wherein the first λ / 4 member has a thickness of 5 μm or less.
11. The display system according to claim 8 , wherein the first retardation member further includes another retardation layer.
12. The absolute value of the difference between the linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member in the absorption axis direction at 25° C. to 65° C. of the first phase difference member when the optical laminate is formed is 2.5×10 -4 9. The display system of claim 8, wherein the temperature is 100° C. or higher.
13. The absolute value of the difference between the linear expansion coefficient of the polarizing member in the transmission axis direction at 25° C. to 65° C. and the linear expansion coefficient of the polarizing member in the transmission axis direction at 25° C. to 65° C. of the first phase difference member when the optical laminate is formed is 1.1×10 -4 9. The display system of claim 8, wherein the temperature is 100° C. / ° C.
14. The display system of claim 8, wherein the ratio of the absolute value of the difference between the linear expansion coefficient of the polarizing element in the absorption axis direction at 25°C to 65°C and the linear expansion coefficient of the polarizing element of the first phase difference element in the absorption axis direction at 25°C to 65°C when formed into the optical laminate to the absolute value of the difference between the linear expansion coefficient of the polarizing element in the transmission axis direction at 25°C to 65°C and the linear expansion coefficient of the polarizing element of the first phase difference element in the transmission axis direction at 25°C to 65°C when formed into the optical laminate is 0.6 or less.
15. 9. The display system according to claim 8, wherein an absolute value of a difference between an in-plane retardation (a) of the first λ / 4 component and an in-plane retardation (b) of the second λ / 4 component is 3.5 nm or less.
Citation Information
Patent Citations
Laminate for organic el displays and circular polarizing plate used therefor
JP2021103286A